Identification and in silico study of a novel dipeptidyl peptidase IV inhibitory peptide derived from green seaweed Ulva spp. hydrolysates - Cian, Raúl Esteban (2022)
A number of functional foods containing seaweed-derived peptides are currently commercialized. Some seaweed derived peptide-containing products include Wakame peptide® and Nori peptide S®. To develop functional foods with the addition of Ulva spp. peptides, the isolation and identification of dipeptidyl peptidase IV (DPP-IV) inhibitory peptides from hydrolysates of this seaweed was performed. Ulva spp. peptides were fractionated and purified sequentially by anion exchange, ultrafiltration, and reversed phase high performance liquid chromatography. The fractions obtained from each analytical step were collected and the in vitro enzyme inhibitory activity was evaluated. The applied purification process increased the in vitro DPP-IV inhibitory activity. The inhibition mechanism of DPP-IV of the most active fraction was evaluated and it was analyzed by MALDI-TOF. A peptide SLAVSVH was identified. It has 57% of hydrophobic residues in their sequence (including Ala and branched chain amino acids), which could be a common feature among inhibitory peptides of DPP-IV. Molecular docking analysis showed that SLAVSVH/DPP-IV complex was stabilized by CH–π interactions between the side chains of Val6 with the indol of Trp629, and between rings of His7 with Trp563. The energy values obtained for the peptide under study indicate that it is a good candidate to inhibit DPP-IV.